Functionalization and exfoliation of graphite with low temperature pulse plasma in distilled water. Issue 9 (17th February 2022) - Letoffé, Adrien; Cuynet, Stéphane; Noel, Cédric; de Poucques, Ludovic; Royaud, Isabelle; Hérold, Claire; Henrion, Gérard; Ponçot, Marc; Fontana, Sébastien
Abstract : The plasma process discussed herein is a new way to exfoliate graphite and to produce functionalized graphenic materials. Abstract : Graphene materials exhibit extraordinary properties, but are difficult to produce. The present work describes the possibility of using a plasma process to exfoliate and functionalize graphite flakes. An impulse plasma phase is generated at a liquid surface to produce chemical species and shock waves in order to modify the reactive liquid as well as the graphite flakes. With this process, industrial graphite was treated. 20% thickness diminution was observed, and the formation of a random turbostratic structure. The exfoliation occurs with small amount of functionalization of the surface. Even after treatment, the graphite flakes present a low defect density compared with other treated graphite obtained by more conventional chemical treatments. This process is a new way to exfoliate graphite and to produce functionalized graphenic materials.